Analyzing QoS factor in 5G communication using optimized data communication techniques for E-commerce applications - Pethuraj, Mohamed Shakeel; Mohd Aboobaider, Burhanuddin; Salahuddin, Lizawati (Elsevier GmbH, 2023)
The fifth generation (5 G) communication is characterized using gigabyte data speeds and ultra-low latency features. Therefore, service providers and mobile networks exploit this technology for real-time applications, including E-commerce. The peak data request in an E-commerce application/ website increases with consumer density and demands. The prime requirement in such environments is data optimization for controlling network traffic and sustaining Quality of Service (QoS). For providing a stabilized data handling procedure for E-commerce applications, this article introduces a Contingent Data Optimization Technique (CDOT). This technique provides multi-resource allocation rather than data compression, depending on the peak utilization. The application-specific data generation and communication are identified for network radio-resource allocation that satisfies the 5 G compliance. The decisions on application data peak and distributions are assured using federated learning. In this process, the network devices are monitored for the least and peak data movements for which the radio resources that deform stagnancy are allocated. The federated learning tunes the allocation recommendation using the resource to data mapping during the peak data span. This technique’s performance is validated using data handling rate, application response, delay, backlogs, and peak utilization.